(untitled) (Oxford, UK, 2000)
This is a Practice tests for the TOEIC test. Lin Lougheed is a well-known ELT figure with particular expertise in writing prep courses for TOEIC. He has written Oxford Practice Tests for the TOEIC Test for OUP, as well as numerous TOEIC preparation texts and skills materials for other publishers.
Keywords: English language,Test of English for International Communication--,Kiểm tra tiếng Anh giao tiếp quốc tế,Tiếng Anh